The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/meg.0b013e32832973fc
|View full text |Cite
|
Sign up to set email alerts
|

Human telomerase activity, telomerase and telomeric template expression in hepatic stem cells and in livers from fetal and postnatal donors

Abstract: Background-Even though telomerase activity has been analyzed in various normal and malignant tissues, including liver, it is still unknown to what extent telomerase can be associated with specific maturational lineage stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Dysregulation of telomerase activity results in uncontrolled malignant tumor growth [Dhaene et al, 2000]. Several studies have shown that cancer cells also have increased telomerase activity which stops telomere shortening and enhances their self‐renewal ability and resistance to apoptosis, effectively rendering them immortal [Fujiwara, 2009; Proctor et al, 2009; Schmelzer and Reid, 2009; Shaker et al, 2009].…”
mentioning
confidence: 99%
“…Dysregulation of telomerase activity results in uncontrolled malignant tumor growth [Dhaene et al, 2000]. Several studies have shown that cancer cells also have increased telomerase activity which stops telomere shortening and enhances their self‐renewal ability and resistance to apoptosis, effectively rendering them immortal [Fujiwara, 2009; Proctor et al, 2009; Schmelzer and Reid, 2009; Shaker et al, 2009].…”
mentioning
confidence: 99%
“…Telomeres may shorten through the advancement of age, as well as other processes that damage the cell . Telomerase activity may help to abrogate this change by adding telomeric repeats on to the end of chromosomes, but it appears that this only occurs in foetal livers . Four groups have studied the relationship between telomere length and ageing in humans …”
Section: Telomeresmentioning
confidence: 99%
“…21,22 Telomerase activity may help to abrogate this change by adding telomeric repeats on to the end of chromosomes, but it appears that this only occurs in foetal livers. 23 Four groups have studied the relationship between telomere length and ageing in humans. 6,[24][25][26] In one of the first studies of telomeres in human liver samples derived from liver resections, Aikata et al reported a reduction rate of 120 bp in 23 individuals (aged 17-81 years) with telomere length reducing to 10 kbp at the age of 80.…”
Section: Telomeresmentioning
confidence: 99%
“…Toutefois le phénotype des cellules isolées n'est pas encore complètement défini. De plus, l'activité télomérase mise en évidence dans les foies foetaux est inexistante dans les cellules souches dérivées des foies nouveau-nés [42].…”
Section: Autres Types De Cellules Souches Sources Potentielles D'hépaunclassified